On harmonic curvatures of null curves of the AW(k)-type in Lorentzian space - Kulahci, Mihriban; Bektas, Mehmet; Erguet, Mahmut (Walter de Gruyter Gmbh, 2008)
We investigate null curves of the AW(k)-type (1 <= k <= 3) in the 3-dimensional Lorentzian space, L-3, and give curvature conditions of these curves by using the Cartan frame. Moreover, we study harmonic curvatures of curves of AW(k)-type and show that if the alpha Frenet curve is of type AW(1), then a is a null helix.
Keywords: null curve; harmonic curvature; Frenet formulas; AW(k)-type curve